The sedimentological and Arsenic contamination history of Frame Lake, Yellowknife, Northwest Territories, Canada - Menard, Etienne (2018)
Frame Lake, a small (88.4 ha), shallow (< 6.5m), high-latitude lake near Yellowknife was selected to test the feasibility of using sub-bottom profiling to estimate total volumes of heavy metal contaminated sediments in lacustrine environments. Physical and ICP-MS analyses were carried out on freeze cores collected from Frame Lake, sedimentological marker beds and 14C dating was used to chronologically constrain depositional history. ICP-MS results showed high levels of arsenic contamination (~1538 µg g-1) in recent sediments results in distinct seismic reflectors, which contrasts sharply with measured Holocene values of 16 µg g-1 (n=41, ± 5.4 SD). Comparison of core data against sub-bottom profiler transect results permitted an interpolated reconstruction of contaminated sediments throughout the lake. Based on our analysis, a minimum of ~230,000 m3 of contaminated sediments would need to be dredged from Frame Lake to achieve a minimum residual sediment arsenic concentration of < 150 µg g-1.